1994
DOI: 10.1073/pnas.91.7.2464
|View full text |Cite
|
Sign up to set email alerts
|

Quest for life-long protection by vaccination.

Abstract: Life-long protection from disease through immunization can be accomplished through individual or com-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…The result of this study showed that top 3 attributes with the highest weight from respondents were reported to be premature deaths averted per year (19.49%); incident cases prevented per year (15.55%); and cost-effectiveness (13.10%). The result on this study strengthened the result from previous studies, which confirmed that the great potential of vaccinations on reducing VPDs and the cost-effectiveness of vaccinations were major factors on the investment of vaccination [31][32][33]. A study by Quilici et al in 2015, reported that vaccination programs represent a long-term investment in future generations since vaccinations have contributions to improve population health and economic growth [31].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The result of this study showed that top 3 attributes with the highest weight from respondents were reported to be premature deaths averted per year (19.49%); incident cases prevented per year (15.55%); and cost-effectiveness (13.10%). The result on this study strengthened the result from previous studies, which confirmed that the great potential of vaccinations on reducing VPDs and the cost-effectiveness of vaccinations were major factors on the investment of vaccination [31][32][33]. A study by Quilici et al in 2015, reported that vaccination programs represent a long-term investment in future generations since vaccinations have contributions to improve population health and economic growth [31].…”
Section: Discussionsupporting
confidence: 84%
“…Specifically, mortality rate and incident case due to VPDs were strongly associated with a country's economic, social conditions and the performance of its healthcare system [31]. In addition, vaccination has been highlighted to be one of the most cost-effective health interventions to save people's lives, improve health and ensure long-term prosperity due to the lifelong protection that vaccines can provide in most cases [32]. Vaccination also could impact the long-term development in a country through economic benefits, such as cognitive development, educational attainment, labor productivity, income, savings, and investment [33].…”
Section: Discussionmentioning
confidence: 99%
“…Mass vaccination is an important measure for the control of infectious diseases [1]. Vaccination protects directly on an individual level and indirectly on a community level.…”
Section: Introductionmentioning
confidence: 99%
“…1 In the Netherlands, MMR vaccination was implemented in 1987 by offering vaccinations to children at the age of 14 months and 9 y As a consequence, the annual mumps incidence decreased dramatically as in other countries where mumps vaccination was implemented. 2,3 Although it was assumed that mumps vaccination induces life-long protection, 4 several mumps outbreaks, especially among vaccinated student populations, have been reported during the last decade in various countries where mumps vaccination has been implemented into their national immunization programs. [5][6][7][8][9][10][11][12][13][14] In 2009-2012, a mumps epidemic (genotype G) arose that spread across multiple locations within the Netherlands, in which also primarily vaccinated students were affected.…”
Section: Introductionmentioning
confidence: 99%